2017
DOI: 10.1089/cell.2016.0035
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Human Amniotic, Chorionic, and Umbilical Cord Multipotent Mesenchymal Stem Cells Regarding Their Capacity for Differentiation Toward Female Germ Cells

Abstract: Placenta harbors a plentiful source of various cells with stem cells or stem-like cell properties, which can be used in therapeutic procedures and research. Mesenchymal stem cells (MSCs) have attracted much attention due to their specific differentiation potential and tolerogenic properties. MSCs have been isolated from different parts of placenta; however, in this study, we isolated MSCs from amnion and chorion membrane, as well as umbilical cord (Wharton's jelly [WJ]) and compared their capacity regarding di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Previous studies have shown that UCMSCs presumably function through the paracrine pathway. In other words, they enhance the environmental factors surrounding the ovarian milieu to better function without differentiating into any of the follicular elements, neither oocytes or granulosa cells due to the absence of evaluating evidence of any meiotic marker to confirm that these cells are haploid [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that UCMSCs presumably function through the paracrine pathway. In other words, they enhance the environmental factors surrounding the ovarian milieu to better function without differentiating into any of the follicular elements, neither oocytes or granulosa cells due to the absence of evaluating evidence of any meiotic marker to confirm that these cells are haploid [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor (EGF) released from hPMSCs improved premature ovarian insufficiency via NRF2/ HO-1 activation [64]. The derivation of germ cells, both female and male, was possible in vitro from placentaderived MSCs [65]. To date, no studies have described the role of hPMSC-derived exosomes (hPMSCs-EXOs) in POF.…”
Section: Human Placenta-derived Mscs Characteristics Of Human Placentmentioning
confidence: 99%
“…By now, cells from the amniotic and chorionic membranes, placental villi, and umbilical cord have been successfully isolated, phenotyped, and characterized [ 74 , 75 ]. Protocols based on trypsin, collagenase, or dispase digestion are used to isolate the cells from the fetal membranes.…”
Section: Isolated Placental Cellsmentioning
confidence: 99%